Case report: Novel deletions in the 6p21.33 involving the CSNK2B gene in patients with Poirier-Bienvenu neurodevelopmental syndrome and literature review - Zhang, Xuan; Lu, Hongjuan; Ji, Yichen; Sun, Wei (Frontiers in Medicine, 2024)
Background Seizures have been identified in most patients with CSNK2B-related Poirer-Bienvenu Neurodevelopment syndrome (POBINDS). Detailed descriptions of seizure phenotypes, various genotypes, and long-term follow-up visits are required for clinicians to provide reasonable clinical management for such patients. Case summary We report two new Chinese patients with varying sizes of 6p21.33 deletions encompassing the CSNK2B gene who presented with intellectual disability and seizures. Furthermore, we conducted a literature review of previously reported patients with 6p21.33 deletions or CSNK2B variants. We summarized and analyzed the clinical characteristics of these patients with seizures. The occurrence of a biphasic pattern of epilepsy and pharmacoresistant epilepsy in patients with CSNK2B variants is severely underestimated. One of our patients underwent a long follow-up period and presented with comprehensive disease progression. Conclusion Our data suggest that the CSNK2B variant or 6p21.33 deletion should be considered in patients with intellectual disability and epilepsy, especially those characterized by biphasic patterns and digital anomalies.